Establishment of genetically encoded H2O2 probes and dynamic measurements of H2O2 levels in the malaria parasite Plasmodium falciparum - Rahbari, Mahsa; Justus Liebig University Giessen (My University, 2017)
Malaria, caused by the apicomplexan parasite Plasmodium falciparum (P. falciparum), is still one of the world s most severe human infectious diseases and threatens the health and life of millions of people, mainly those living in tropical and subtropical regions, despite strong eradication efforts. P. falciparum depends on its complex antioxidative system based on thioredoxin and glutathione for survival. The intraerythrocytic parasite lives in a pro-oxidant environment, and the host immune response increases the oxidative burden on the parasite, which can cause major oxidative damage. Interfering with the parasites essential redox system is a promising target for malaria-eradicating drugs. Several antimalarial drugs are supposed to mediate their effects at least partially by increasing reactive oxygen species (ROS) in the parasite. ROS are highly reactive and damaging towards DNA, lipids and proteins. Hydrogen peroxide (H2O2) is one of the most important cellular ROS. Until now, neither molecular targets nor regulatory mechanisms and dynamic changes of H2O2-mediated signaling in P. falciparum are known. The development of the genetically encoded H2O2 sensors roGFP2-Orp1 and HyPer paved the way for non-disruptive, ratiometric, real-time, dynamic, and specific measurements of changes in H2O2 concentrations within a living cell. Studying the dynamics of H2O2 signaling in parasites exposed to antimalarial drugs can lead to a better comprehension of their molecular mode of action and give further insights into the development of future chemotherapeutic agents. In this work, the ratiometric H2O2 redox sensors roGFP2-Orp1 and HyPer-3 and the pH-insensitive version of HyPer (SypHer) were successfully transiently expressed in the cytosol of blood stage P. falciparum parasites and their functionality was systematically characterized in vitro and in cell culture. Both redox probes showed reproducible sensitivity towards H2O2 in the lower micromolar range in vitro and in cell culture. Due to the pH sensitivity of HyPer-3, parasites expressing roGFP2-Orp1 were used for evaluating the short, medium, and long-term effects of antimalarial drugs on H2O2 levels and detoxification in Plasmodium in combination with confocal live-cell imaging. None of the quinolines or artemisinins tested had significant effects on H2O2 homeostasis at pharmacologically relevant concentrations. However, pre-treatment of the cells with antimalarial drugs or heat shock led to a higher tolerance towards exogenous H2O2. Based on the data, both roGFP2-Orp1 and HyPer-3 probes are reliable and valuable tools for studying H2O2 metabolism in living malaria parasites. However, the necessity to use a pH probe in parallel makes utilizing HyPer-3 more challenging and time consuming.Determination of the effects of oxidative and pharmacological stress on the H2O2 homeostasis was optimized by stably integrating the redox sensor roGFP2-Orp1 into the genome of P. falciparum using the attB/attP integration method. Stable genomic integration overcomes limitations of transient transfection of the probes, allowing more detailed in-cell studies. For the first time H2O2 dynamics in the mitochondrial subcellular compartment could be determined using the stably integrated Mito-roGFP2-Orp1 redox probe. In both cytosol and mitochondrion, the sensors showed reproducible sensitivity towards H2O2 in the low micromolar range and towards antimalarial compounds at pharmacologically relevant concentrations. Upon short-term exposure (4 h), artemisinin derivatives, quinine and mefloquine impacted H2O2 levels in mitochondria, whereas chloroquine and G6PD inhibitors affected the cytosol; 24 h exposure to an arylmethylamino steroid and G6PD inhibitors revealed oxidation of mitochondria and cytosol, respectively. Furthermore, the redox sensors hGrx1-roGFP2 (glutathione sensor) and sfroGFP2 were expressed in the cytosol of NF54-attB blood-stage P. falciparum parasites. Prior to stable integration, studies with the episomal transfected hGrx1-roGFP2 strain were performed. Both sensors were evaluated with regard to their sensitivity towards oxidative stress in cell culture. The results showed that G6PD inhibitors and the arylmethylamino steroid disturb GSH (reduced glutathione) redox ratio in either 4 h or 24 h incubations. The redox sensors hGrx1-roGFP2 and sfroGFP2 are both reliable tools for studying redox metabolism in malaria parasites with comparable oxidation/reduction sensitivities, at which sfroGFP2 appeared to exhibit a more pronounced fluorescence intensity. Microscopic and plate reader-based detection methods were directly compared in order to evaluate plate reader-based measurement of bulk cell cultures as an alternative for single live-cell imaging. It is now possible to investigate quickly and efficiently with high reproducibility direct responses and long-term effects of compounds on H2O2/GSH homeostasis in cell populations.

Tropische Malaria, verursacht durch den einzelligen Parasiten Plasmodium falciparum (P. falciparum), stellt noch immer eine der weltweit schwerwiegendsten Infektionskrankheiten dar. Trotz intensiver Bemühungen die Malaria auszurotten, bedroht sie hauptsächlich in tropischen und subtropischen Regionen der Erde die Gesundheit und das Leben von Millionen von Menschen.P. falciparum ist in hohem Maße von seinen komplexen antioxidativen Systemen, insbesondere dem Thioredoxin- und dem Glutathionsystem, abhängig. Der intraerythrozytäre Parasit lebt in einer pro-oxidativen Umgebung und die Immunantwort des Wirtes erhöht zusätzlich den oxidativen Stress auf den Erreger. Das Eingreifen in den Redoxstoffwechsel des Parasiten stellt daher ein vielversprechendes Ziel für neue Wirkstoffe gegen Malaria dar. Mehrere Malariamedikamente vermitteln bereits jetzt ihre Wirkungen zumindest teilweise durch das Erhöhen der Konzentrationen von reaktiven Sauerstoffspezies (ROS) im Parasiten, wodurch DNA, Lipide und Proteine geschädigt werden können. Wasserstoffperoxid (H2O2) ist eine der wichtigsten zellulären ROS. Bislang waren molekulare Targets von H2O2, H2O2-vermittelte Signaltransduktion sowie dynamische Veränderungen der H2O2-Konzentration in P. falciparum wenig untersucht. Die Entwicklung der genetisch kodierten H2O2-Sensoren roGFP2-Orp1 und HyPer haben den Weg für ratiometrische, dynamische und hochspezifische Echtzeitmessungen der H2O2-Konzentrationen in lebenden Zellen geebnet. Das Erforschen der H2O2-Dynamik in Parasiten, die Malariamedikamenten ausgesetzt sind, kann zu einem besseren Verständnis ihrer molekularen Wirkungsweise und zu weiteren Erkenntnissen für die Entwicklung von zukünftigen Chemotherapeutika beitragen.In der vorliegenden Arbeit wurden die ratiometrischen H2O2-Redoxsensoren roGFP2-Orp1 und das pH-sensitive HyPer-3 sowie die pH-insensitive Version von HyPer (SypHer) im Zytosol von P. falciparum Blutstadien erfolgreich transient exprimiert und ihre Funktionalität systematisch in vitro und in Zellkultur charakterisiert. Beide Redoxsonden haben eine reproduzierbare Sensitivität in Bezug auf H2O2 im unteren mikromolaren Bereich in vitro und in Zellkultur. Aufgrund der pH-Sensitivität von HyPer-3, wurden nur in roGFP2-Orp1 exprimierenden Parasiten mittels konfokalem live-cell imaging Kurz-, Mittel- und Langzeiteffekte von Malariamedikamenten auf H2O2-Konzentrationen und Entgiftung analysiert. Keines der getesteten Quinoline oder Artemisinine zeigte in pharmakologisch relevanten Konzentrationen eine signifikante Wirkung auf die H2O2-Homöostase. Allerdings führte die Vorbehandlung der Zellen mit Malariamedikamenten oder Hitzeschock zu einer höheren Toleranz gegenüber exogenem H2O2. Auf diesen Daten basierend, sind beide Sonden, roGFP2-Orp1 und HyPer-3, zuverlässige und wertvolle Instrumente, um den H2O2-Metabolismus in lebenden Malariaparasiten zu erforschen. Die Notwendigkeit, zeitgleich mit HyPer-3 eine pH-Sonde als Kontrolle einsetzen zu müssen, macht die Verwendung von roGFP2-Orp1 allerdings deutlich leichter. In einem zweiten Schritt wurde die Bestimmung der Effekte von oxidativem und pharmakologischem Stress auf die H2O2-Homöostase weiter optimiert. Dies gelang durch die stabile Integration des Redoxsensors roGFP2-Orp1 in das Genom von P. falciparum mittels der attB/attP-Methode. Stabile genomische Integration hebt die multiplen Einschränkungen einer transienten Transfektion der Sonden auf, was deutlich detailliertere Zellstudien erlaubt. Mittels des stabil integrierten Mito-roGFP2-Orp1 Redoxsensors konnten somit zum ersten Mal H2O2-Dynamiken in einem subzellulären Kompartiment, hier dem Mitochondrium, bestimmt werden. Sowohl im Zytosol als auch im Mitochondrion zeigten die Sensoren reproduzierbare Sensitivität gegenüber H2O2 im unteren mikromolaren Bereich und gegenüber Malariamedikamenten in pharmakologisch relevanten Konzentrationen. Bei der Kurzzeit-Inkubation (4 h) zeigten Artemisinin-Derivate, Chinin und Mefloquin deutliche Effekte auf H2O2-Konzentrationen in Mitochondrien, wogegen Chloroquin und Glucose-6-Phosphat-Dehydrogenase Inhibitoren besonders das Zytosol beeinflussten. Eine 24 h Inkubation mit einem Arylmethylaminosteroid und mit G6PD Inhibitoren zeigten eine deutliche Oxidation von Mitochondrien und Zytosol.Parallel zu den H2O2-Sonden wurden die Redoxsensoren hGrx1-roGFP2 (Glutathionsensor) und sfroGFP2 stabil in das Genom von P. falciparum integriert und im Zytosol von NF54-attB Blutstadienparasiten exprimiert. Vorausgegangen waren auch hier Untersuchungen mit episomal transfizierten Zellen. Beide Sensoren messen das intrazelluläre glutathionabhängige Redoxpotenzial und wurden hinsichtlich ihrer Sensitivität auf oxidativen Stress in der Zellkultur evaluiert. In 4 h und 24 h Inkubationen wurden deutliche Effekte von G6PD Inhibitoren und dem Arylmethylaminosteroid auf das Redoxpotenzial gemessen. Dabei erwiesen sich beide stabil integrierten Sensoren, hGrx1-roGFP2 und sfroGFP2, als zuverlässige Instrumente mit vergleichbaren Oxidation-/Reduktion-Sensitivitäten, wobei sich sfroGFP2 durch eine stärkere Fluoreszenzintensität auszeichnete. Mikroskopische und Plattenleser-basierte Detektionsmethoden wurden für die Sonden direkt miteinander verglichen, um Plattenleser-basierte Messungen von Zellpopulationen als Alternative zur Einzelzell-Visualisierung zu evaluieren. Auf Basis dieser Arbeiten ist es nun möglich, die H2O2/GSH-Homöostase von Zellpopulationen schnell und effizient mit einer hohen Reproduzierbarkeit zu untersuchen.
Etablierung von genetisch kodierten H2O2-Sonden und dynamischen Messungen von H2O2-Leveln im Malaria-Parasiten Plasmodium falciparum
Keywords: Plasmodium falciparum; Malaria; H2O2; genetisch kodierte Redoxsonden; Plasmodium falciparum; Malaria; H2O2; genetically encoded redox probes; ddc:570